FOLK SONG ADAPTATIONS FOR MEN’S CHOIR BY JÁNOS SEPRŐDI - PÉTER, Éva (Studia Universitatis Babes-Bolyai Musica, 2018)
Music historian and folklorist János Seprődi deceased 95 years ago. He played a significant part in the Transylvanian folk song collecting endeavours. A predecessor to Kodály and Bartók he published some of his folk song collections from the region of Marosszék already in 1901. In the paper hereby I intend to write about the folk songs he collected and the 57 pieces for men’s choir based on these collections.